Malaysian Administrative Law: Recent Case Law Development - Gan, CC (Journal of Malaysian and Comparative Law, 2019)
Administrative lawyers who have followed closely the case law development in Malaysian Administrative Law over the last seven years or so will notice that our law has picked itself up gradually after the disastrous case of United Engineers (M) Bhd v Lim Kit Siang and developed with greater momentum and confidence since of late. The following pages will be devoted to tracing and analysing that development. The cases covered in this article will be dealth with under four sub-headings of preventive detention, employment, Interpretation of privative clauses, and public authorities' liabilities. It must be noted that this article only focuses selectively on the positive aspects of the development referred to.